Draconema brasiliensis and Draconema fluminensis (Chromadorida, Draconematidae): two new species of free living nematodes from a rocky shore affected by upwelling on the Brazilian coast - Venekey, Virág; Lage, Luciana Monteiro; Da Fonsêca-Genevois, Verônica (Zootaxa, 2005)
Two new species of Draconematidae from a rocky shore affected by upwelling on the Brazilian coast are described. Draconema brasiliensis sp. n. and Draconema fluminensis sp. n. are the first species within the Draconema genus with more than 14 post-rostral enlarged annules (15ñ16 in the new species). Both species are close to D. cephalatum in many measurements but despite some similarities they have longer gobernaculum, D. fluminensis presents 7 pairs of setae on the non-annulated region of the tail (D. cephalatum presents only 6) and D. brasiliensis has a longer tail. On the rocky shores prospected, only the two species were found within Draconematidae.